STRATEGIES OF ISLAMIC RELIGIOUS EDUCATION TEACHERS TO INCREASE LEARNING INTEREST IN STUDENT AFTER THE COVID-19 AT SD MUHAMMADIYAH 04 BINJAI - Fadhilah Juliandari; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2022)
: Online learning is a learning system without face to face directly between teachers and students,which is carried out online using the internet network. For more than two years, students have been forced to carry out online learning due to the Covid-19 pandemic. With the Covid-19 pandemic, some students complained because they felt that online learning was less effective. Many distractions that make their learning process is not optimal. The problem in this research is how to increase student interest in after Covid-19 pandemic student learning at Sd Muhammadiyah 04 Binjai. The purpose of this study was to describe the strategy of Islamic Religious Education teachers to increase student interest in learning at Sd Muhammadiyah 04 Binjai. The benefits of this research are expected to increase the witers insight and insight about the strategy of Islamic Religius Education teacher on interest in learning at Sd Muhammadiyah 04 Binjai. This research is a qualitative research. The subjects of this study were teachers and students at Sd Muhammadiyah 04 Binjai. Data collection is the process of seeking data by means of observation, interviews and documentation.Keyword : PAI Teacher Strategy, Interest in Learning, After the Covid-19